Air Laut Dalam Perspektif Hadis Dan Sains: Analisis Makna Ṭahuūr Dan Relevansinya Dengan Kimia - Muklihah Muklihah; Hikmatul Izzah; Qurrotu A’yun (AR ROSYAD: Jurnal Keislaman dan Sosial Humaniora, 2025)
Abstract: This study aims to examine the hadith of the Prophet Muhammad (peace be upon him) about the purity of seawater from the perspective of hadith and modern science, especially regarding the meaning of ṭahūr (holy and purifying) and the content of chemical elements of seawater. The hadith that became the object of study was the words of the Prophet (peace and blessings of Allaah be upon him): "The sea is holy in its waters, and its carcasses are lawful"), which was narrated by Abū Dāud, al-Tirmiżī, al-Nasā'ī, and Ibn Mājah through the path of the sanad ṣaḥīḥ. The methods used in this study are takhrij and iʿtibār sanad to trace the validity of hadith narration, followed by hadith lectures and interdisciplinary analysis through modern scientific approaches. The results of the study show that the hadith has the status of ṣaḥīḥ and has an important legal value in the jurisprudence of ṭahārah, namely that seawater is an absolute water that is sacred and can be used for purification (ṭahūr). From a scientific perspective, seawater is chemically composed of the elements chlorine (Cl), sodium (Na), magnesium (Mg), calcium (Ca), sulfur (S), and potassium (K), with a salinity level of about 3.5%. The high salt content makes seawater antiseptic and antimicrobial, so it can naturally inhibit the growth of microorganisms that cause feces or decay. In addition, the very large volume of seawater makes it able to carry out a self-purification process against contamination.